Association of impaired lung function with dementia, and brain magnetic resonance imaging indices: a large population-based longitudinal study. (20th November 2022) - Zhou, Lihui; Yang, Hongxi; Zhang, Yuan; Li, Huiping; Zhang, Shunming; Li, Dun; Ma, Yue; Hou, Yabing; Lu, Wenli; Wang, Yaogang
Abstract: Objective: to examine the association between different patterns of impaired lung function with the incident risk of dementia and magnetic resonance imaging (MRI)-based brain structural features. Methods: in UK Biobank, a total of 308, 534 dementia-free participants with valid lung function measures (forced expiratory volume in 1 s [FEV1 ] and forced vital capacity [FVC]) were included. Association was assessed using Cox proportional hazards regression model. Furthermore, the association between impaired lung function and brain MRI biomarkers related to cognitive function was analysed among 30, 159 participants. Results: during a median follow-up of 12.6 years, 3, 607 incident all-cause dementia cases were recorded. Restrictive impairment (hazard ratio [HR], 1.42; 95% confidence interval [CI], 1.27–1.60) and obstructive impairment (HR, 1.28; 95% CI, 1.15–1.42) were associated with higher risk of all-cause dementia. The restricted cubic splines indicated FEV1 % predicted and FVC % predicted had reversed J-shaped associations with dementia. Participants with impaired lung function have higher risks of all-cause dementia across all apolipoprotein E ( APOE ) risk categories, whereas associations were stronger among those of low APOE risk ( P for interaction = 0.034). In addition, restrictive and obstructive impairment were linked to lower total (β: −0.075, SE: 0.021, P fdr  = 0.002; β: −0.033, SE: 0.017, P fdr  = 0.069) and frontoparietal grey matter volumes, higher white matter hyperintensity, poorer white matter integrity, lower hippocampus (β: –0.066, SE: 0.024, P fdr  = 0.017; β: –0.051, SE: 0.019, P fdr  = 0.019) and other subcortical volumes. Conclusions: participants with restrictive and obstructive impairments had a higher risk of dementia. Brain MRI indices further supported adverse effects and provided insight into potential pathophysiology biomarkers.